Why are medical students 'checking out' of active learning in a new curriculum?. Issue 3 (March 2014) - White, Casey; Bradley, Elizabeth; Martindale, James; Roy, Paula; Patel, Kunal; Yoon, Michelle; Worden, Mary Kate
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at 'discuss'